Botanicals Reduce Circulating Concentrations of Cholesterol and Triglycerides and Work Synergistically With Arachidonic Acid to Reduce Inflammatory Cytokines in Cats - Jewell, Dennis E.; Panickar, Kiran S. (Frontiers in Veterinary Science, 2021)
Forty Eight cats were used to measure the effects of feeding a traditional adult cat food supplemented with either arachidonic acid (ARA), a botanical mix (botanicals) or both on circulating biochemical parameters and inflammatory cytokines. The cats were healthy adults (mean age, 3.0; range, 1.3–6.4 years). The adult cats were fed one of four foods (n = 12 per group) for 84 days (dietary changes reported as fed): a traditional adult cat food (control, 0.05% ARA no added botanicals), or control food supplemented with arachidonic acid from chicken liver (0.13% ARA when supplemented), control food supplemented with botanicals (green tea 0.5%, fenugreek 0.05%, and tulsi 0.003%), and control plus ARA (0.13% as fed) with botanicals (green tea 0.5%, fenugreek 0.05%, and tulsi 0.003%). Response variables were compared between treatments: initially, and at 84 days (end of study). The measurements were standard complete blood counts and chemistries as well as circulating cytokines. Botanical inclusion reduced (P < 0.05) circulating cholesterol and triglycerides while arachidonic acid increased (P < 0.05) their concentrations. The pro-inflammatory cytokines MCP-1, TNFα, SDF-1, Flt3L, IL-8, IL-12p40, IL-13, and IL-18 were all reduced (P < 0.05) in cats after consuming the ARA + botanicals food for 84 days with little change after consuming the other foods. Therefore, this combination of ARA and botanicals may be of value in reducing inflammation.